O efeito da NBC TG 48 na adoção voluntária do hedge accounting por companhias listadas na B3 - Konzen, Juliano (Universidade do Vale do Rio dos Sinos, 2020)
This dissertation aimed to describe the effect of NBC TG 48 on the voluntary adoption of hedge accounting by companies listed on B3. A logistic regression was used to analyze the relationship between the adoption of HA and NBC TG 48. The sample was composed of 214 companies that had their shares traded on B3 in 2017 and 2018, a period that covers one year before and one year after the entry into force of NBC TG 48. The results of the descriptive analysis indicate that, in the period, there was a growth of only 10% in the number of companies that voluntarily adopted HA. The results of the logistic regression point to a positive, but not significant, relationship between NBC TG 48 and the voluntary adoption of HA. In other words, the decrease in the complexity of the rules for the adoption of HA provided by NBC TG 48, did not strongly motivate companies to use this special accounting methodology and to enjoy the benefits provided by it, regardless of the economic sector to which they belong. However, other factors pointed out in the literature, such as size, indebtedness, exports, imports and big four, have a positive and significant relationship with the voluntary adoption of HA. In short, the probability of voluntary adoption of HA is greater in larger companies; more indebted; who practice export and/or import operations; and are audited by big four.
Keywords: Hedge accounting; Adoção voluntária; NBC TG 48; Voluntary adoption; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis